Badanie relacji między zróżnicowaniem pojedynczych modeli a błędem modelu zagregowanego - Rozmus, Dorota (Analysis of Relationship Between Single Models Diversity End Error of Aggregated Model, 2007)
Ensembles become more and more popular in classification and regression problems. Very often they have better empirical and theoretical properties than single models. One factor that is needed in order to get high performance of aggregated model is recognized as models diversity. The paper discusses the problem of ensemble diversity in regression using the idea of ensemble error decomposition introduced by Ueda, Nakano (1995) and Krogh, Vedelsby (1996). We show also results of experiments concerning the relationship between ensemble error and ensemble diversity, measured by means of the two presented decompositions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 195-201